PLURILINGUAL COMPETENCE AS A KEY SKILL FOR THE 21ST CENTURY - Zebuniso Isanova; Samarat Mambetajieva (International Journal of Literature and Language Studies, 2026)
Abstract: The rapid globalization of economic, social, and technological processes has increased the importance of linguistic and cultural diversity in modern societies. In this context, plurilingual competence has emerged as a crucial skill for the 21st century. It enables individuals to use multiple languages flexibly and effectively while navigating diverse cultural environments. This article examines the concept of plurilingual competence, its significance in contemporary education and society, and the benefits and challenges associated with its development. The study argues that fostering plurilingual competence contributes to lifelong learning, intercultural understanding, employability, and active participation in a globalized world.